A Social Network Approach to Research Systemsfor Sustainable Agricultural Development: Results from a Study of Kenya, Ghana, and Kerala - Wesley Shrum (International Service for National Agricultural Research (ISNAR). Briefing Paper #36. 1997., 1997)
The nature and frequency of linkages in developing country research systems has long been a concern of policymakers and research managers for several reasons. One is that research in science and technology requires collaborative relationships as well as effective communication. Another is that the material and informational resources on which research depends often lie outside the organizations in which projects are conducted. A science and technology system may be viewed as a set of people, organizations, and linkages that connect them.